(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sari IA, Murti RH, Misnawi, Putra ETS, Susilo AW. 2021. Sensory profiles of cocoa genotypes in Indonesia. Biodiversitas 23: 648-654. The Cocoa flavor is influenced by genetic factors and has an important role in increasing the added value of beans as specialty products. For this reason, superior genotypes with specific and unique flavors should be identified as fine flavor cocoa (FFC) products. This study was conducted to obtain genotypes with sensory quality and specific profiles. Ten clones under three groups were used: Forastero (KW 516 and KEE 2), Trinitario with purple beans (ICCRI 03, ICCRI 07, ICCRI 09, MCC 02, Sulawesi 1, Sulawesi 2, and TSH 858), and Trinitario with white beans (DR 2). Genotypes were assigned using a completely randomized block design with three replications. A sensory test was performed by three trained and certified panelists using the Indonesian Coffee and Cocoa Research Institute (ICCRI) and Guittard Chocolate Company standards. The attributes, acidity, bitterness, astringency, fresh fruit, browned fruit, floral aroma, woody aroma, spicy, nutty taste, and browned/roasted appearance of cocoa were evaluated on a scale of 1-10. Data were examined through ANOVA, flavor character profiling, PCA Biplot, and dendrogram analysis in STAR 2.0.1, Microsoft Excel 2019, and R Studio. Results showed that the genotypes significantly influenced the chemical content of the beans, and each genotype had a specific flavor character. The genotypes were classified into three groups based on flavor characters via PCA biplot and dendrogram analysis. Two groups of aromatic genotypes had the potential to develop FFC products with weak (DR 2) and strong cocoa taste (ICCRI 09, ICCRI 03, ICCRI 07, MCC 02, and TSH 858). Conversely, the nonaromatic cocoa groups with strong taste were KEE 02, KW 516, Sulawesi 1, and Sulawesi 2. Therefore, the intensity of floral and nutty aromas significantly affected the overall quality of cocoa flavor.